Adherence to antidiabetic therapy: a concept analysis - Mukona, Doreen; Dzimiri, Tafara; Chauke, Lilian; Ndaimani, Augustine; Zvinavashe, Mathilda (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Many diabetic patients do not adhere to their medication regimen. This may be due to patients and healthcare staff having different understanding on what constitutes adherence to antidiabetic therapy. Consequently patients and healthcare staff have not been able to achieve the desired health outcomes. Objectives The aim of this concept analysis is to clarify and define the concept of adherence to antidiabetic therapy. This analysis will provide a common basis for those pursuing a better understanding of patient decision making, reduction of complications and improved long-term adherence to antidiabetic therapy. Methods A concept analysis, utilizing the eight steps Walker and Avant method was done. Eleven articles were reviewed to produce a definition of adherence to antidiabetic therapy. Results Attributes of adherence to antidiabetic therapy includes knowledge of optimal level of blood glucose and home blood glucose monitoring, knowledge of complications from poor glycaemic control, use of daily medication reminders, knowing and agreeing to the medication, active continuous collaboration between patient and health care provider in communicating and negotiating the treatment regimen, and ability to meet outcome targets Conclusion Adherence to antidiabetic therapy is defined as knowing and agreeing to antidiabetic therapy (medication, diet and exercises), active continuous patient participation in negotiation and appraisal of therapy, and consistence in performing desired health behaviours to meet outcome targets. The concept analysis will assist health professionals in standardising treatment guidelines which enables them to continually measure and improve adherence to antidiabetic therapy.